Destination management and reliable information - Herz Castro, Katia Beatriz (2017)
The importance of proper management of tourist destinations is an aspect that is often taken lightly as the information used to define it. The lack of information, biased or misleading information of some concepts, not updated statistics and even a weak primary information obtained, led to the development of projects or initiatives that have not had good results. What information should use, which points are key to define a destination, what activities performed for this purpose and how actors must interact to achieve optimal results, are always aspects that have generated discussion or just have not been taken into account, reaching, often, to «imitate» initiatives which, having been successful in some places, are not always according to our reality. Being Peru a country with so much potential for tourism and many untapped areas, this is an essential issue for the development of tourism as an alternative for local development.